FENOMENA PERJUDIAN DI KALANGAN PELAJAR (Studi Terhadap Penyebab dan Dampak Judi Domino Bagi Pelajar di Nagari Padang Gelugur Kecamatan Padang Gelugur Kabupaten Pasaman) - -, JEFRINALDI - (Pendidikan Sosiologi, 2014)
Base data of Nagaris sponsor office Gelugurs Moorland at gets that gamble booth amount dominos on year 2010, 2014 available 12 student place booths does gambling. On year 2014 available 6 informen which researcher interview. To the effect of observational it is 1. for description student causal factor gets Nagaris gamble Gelugurs Moorland Pasamans Regency, 2. To description dominos gamble impact for student at Nagari Gelugurs Moorland Pasamans Regency. This research utilize kualitatifs approaching with descriptive type. Data collecting tech did by obeservasi, straightforward interview and studi is document. Analisis is data utilizes model Milles and Huberman. Result of this research at Nagari Gelugurs Moorland Gelugurs Moorland district Regency Pasaman is 1. That dominos gamble causal factor at student circle at Nagari Gelugurs Moorland Pasamans Regency which is: 1. Trial and error arena, 2. Opium / addiction, 3. Environmentally, and 4. Economic Factors. Of research result about impact for student what does dominos gambling at Nagari Gelugurs Moorland Pasamans Regency which is: 1. Often hookeys school. 2. Lying oldster, and 3. Defalcate oldster.